Metode Sosiodrama dalam Meningkatkan Kecerdasan Moral Anak - Ahyani, Latifah Nur; Dhania, Dhini Rama (Jurnal Sosial Budaya, 2011)
ChildrenÂ Â  growÂ Â  andÂ Â  developÂ Â  inÂ Â  aÂ Â  lifeÂ Â  coloredÂ Â  byÂ Â  the violationÂ Â  ofÂ Â  othersÂ Â  right,Â Â  crime,Â Â  compulsion,Â Â  ignorance, unclearness between right and wrong, good and bad, allowed and not allowed behaviors. Building moral intelligenceÂ  is very important to do in order that the childrenâs intuition is able to differentiate the right and the wrong. Thus, theyÂ  can reject the bad influences from outside. One of the ways used to give moral value to the children is sociodrama.The research aims to know the sociodrama method in improving the moral intelligence of children. Subject of theÂ  research is the student of elementary school. The number of subject in the experiment and control groups is same thatÂ  is 14 students.The research is design using model of The Untreated Control Group Design with Pretest and Posttest. The design uses two groups examined which consist of an experiment group and a control group. The measurement is conducted twiceÂ  using moral intelligence measurement instrument, namely before it is given treatment (pre-test) and after it has beenÂ  given treatment (post-test).The result of analysis using T-Test shows that there is a difference of moral intelligence achievement level of theÂ  children between those who receive moral value guidance through sociodrama method and those who do not receiveÂ  moral value guidance through sociodrama method p = 0,009 (p<0,05). The result of analysis also shows that there isÂ  difference of moral intelligence achievement level of th children before receiving moral value guidance throughÂ  sociodrama method and after they have receive the moral value guidance through sociodrama method p = 0,033Â  (p<0,05). The result of analysis shows the great contribution of sociodrama method towards the moral intelligence ofÂ  children is 30,9%.